PENGARUH MOTIVASI BELAJAR DAN KEPERCAYAAN DIRI TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Rahayu, Lusy; U.S, Supardi (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2025)
ABSTRACT This study aims to analyze the extent to which learning motivation and self-confidence influence students’ ability to solve mathematical problems among tenth-grade students at SMA Pusaka 1 Jakarta. The background of this research stems from the importance of mathematical problem-solving skills as one of the essential competencies students must possess to face academic challenges, as well as the crucial role of internal factors such as motivation and self-confidence in supporting the learning process. The research employed a quantitative approach with a descriptive method. The sample consisted of 51 students selected through random sampling. Data collection instruments included questionnaires to measure the levels of motivation and self-confidence, and essay tests to assess mathematical problem-solving skills. Before conducting multiple linear regression analysis, the data were first examined using classical assumption tests, namely normality, multicollinearity, and heteroscedasticity tests. The findings showed that learning motivation and self-confidence simultaneously had a significant influence on students’ mathematical problem-solving abilities, as evidenced by an F-value of 29.426 and a significance level below 0.05. Individually, both learning motivation (t = 5.080) and self-confidence (t = 2.726) demonstrated a meaningful effect on problem-solving skills. The coefficient of determination (R²) was 0.551, indicating that 55.1% of the variation in mathematical problem-solving ability can be explained by these two variables, while the remaining 44.9% is influenced by other factors not examined in this study. ABSTRAK Penelitian ini bertujuan untuk menganalisis sejauh mana pengaruh motivasi belajar dan kepercayaan diri terhadap kemampuan peserta didik dalam menyelesaikan masalah matematika pada peserta didik kelas X di SMA Pusaka 1 Jakarta. Latar belakang penelitian ini berakar dari pentingnya kemampuan pemecahan masalah matematika sebagai salah satu keterampilan utama yang harus dimiliki siswa dalam menghadapi tantangan akademik, serta peran penting dari faktor internal seperti motivasi dan rasa percaya diri dalam mendukung proses belajar. Pendekatan penelitian yang digunakan adalah kuantitatif dengan metode deskriptif. Sampel penelitian melibatkan 51 siswa yang dipilih secara acak (random sampling). Alat pengumpulan data meliputi angket untuk mengukur tingkat motivasi dan kepercayaan diri, serta tes esai untuk menilai kemampuan pemecahan masalah matematika. Sebelum melakukan analisis regresi linier berganda, data dianalisis terlebih dahulu melalui pengujian asumsi klasik, yaitu uji normalitas, multikolinearitas, dan heteroskedastisitas. Hasil penelitian memperlihatkan bahwa secara simultan, motivasi belajar dan kepercayaan diri memiliki pengaruh yang signifikan terhadap kemampuan menyelesaikan soal matematika, sebagaimana dibuktikan dengan nilai F hitung sebesar 29,426 dan nilai signifikansi di bawah 0,05. Secara individual, baik motivasi belajar (t = 5,080) maupun kepercayaan diri (t = 2,726) menunjukkan pengaruh yang berarti terhadap kemampuan pemecahan masalah. Nilai koefisien determinasi (R²) sebesar 0,551 mengindikasikan bahwa 55,1% variasi dalam kemampuan pemecahan masalah matematika dapat dijelaskan oleh kedua variabel tersebut, sedangkan sisanya dipengaruhi oleh faktor lain yang tidak diteliti.